Collagen-derived dipeptide prolyl-hydroxyproline promotes osteogenic differentiation through Foxg1 - Kimira, Yoshifumi (Cell Mol Biol Lett, 2017)
Prolyl-hydroxyproline (Pro-Hyp) is one of the major constituents of collagen-derived dipeptides. We previously reported that Pro-Hyp promotes the differentiation of osteoblasts by increasing Runx2, osterix and Col1α1 mRNA expression levels. Here, to elucidate the mechanism of Pro-Hyp promotion of osteoblast differentiation, we focus on the involvement of Foxo1 in osteoblast differentiation via Runx2 regulation and the role of Foxg1 in Foxo1 regulation. The addition of Pro-Hyp had no effect on MC3T3-E1 cell proliferation in Foxo1- or Foxg1-knockdown cells. In Foxo1-knockdown cells, the addition of Pro-Hyp increased ALP activity, but in Foxg1-knockdown cells, it had no effect on ALP activity. An enhancing effect of Pro-Hyp on the Runx2 and osterix expression levels was observed in Foxo1-knockdown cells. However, no enhancing effect of Pro-Hyp on osteoblastic gene expression was observed when Foxg1 was knocked down. These results demonstrate that Pro-Hyp promotes osteoblastic MC3T3-E1 cell differentiation and upregulation of osteogenic genes via Foxg1 expression.